The 2D – 3D – 2D' method for communication system research - Pelishok, Volodymyr (Видавництво Львівської політехніки, 2012)
This paper contains a description of the proposed 2D – 3D – 2D' method, which allows transition from the existing two-dimensional dependences to the ancillary three-dimensional dependences and follows to the required two-dimensional dependences. It helps to simplify the research.
Keywords: antennas; modulation; МATLAB